Kajian Penerapan Konsep Terapi Penyembuhan Pada Panti Jompo di Kota Banda Aceh (Studi Kasus: Rumoh Seujahtra Geunaseh Sayang) - Cut Farah Ziba; Meutia (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The Healing Therapeutic principle is one approach that can be used to create a comfortable and safe environment for the elderly. This principle involves architectural design that affects the psychological and physical aspects of users. In the context of nursing homes, the application of the healing therapeutic principle can improve the quality of life of residents. The purpose of this study is to determine the application of the healing therapeutic concept in the UPTD Social Home for the Elderly Rumoh Seujahtra Geunaseh Sayang, located in Lamglumpang, Ulee Kareng, Banda Aceh.